Solitary parotid duct sialolith in a patient with Sjörgren’s syndrome: Report of a case - Wan Ahmad Kamil, Wan NurHazirah; Hassan, Syahir; Rahman, Fairuz; Burhanudin, Nor Aszlitah; Goh, Yet Ching; Kadir, Kathreena; Siar, Chong Huat (Faculty of Dentistry, University Malaya, 2016)
Sjörgren’s syndrome is an uncommon chronic autoimmune disorder that affects exocrine glands. Sialolithiasis is an obstructive salivary gland disease which is also uncommon in the parotid salivary gland. The existing literature has documented the occurrence of multiple calcifications within the parenchyma of the parotid glands in patients with Sjörgren’s syndrome. This report describes the first case of right parotid duct solitary sialolith formation in a 64 year old female patient with Sjörgren’s syndrome. Whether the salivary stone encountered in this case represents an oral manifestation of Sjörgren’s syndrome or is just a co-incidental finding was discussed.